Study on Primary Sjögren’s Syndrome and Oral Cavity Disorders - Soares, Sandra Clara; Castro, Ana Rita; Chapela, Sara Cendon (New Horizons in Medicine and Medical Research Vol. 2, 2022)
Sjögren’s Syndrome (SS) is one of the three most common autoimmune diseases in the world, characterized by an inflammation of the exocrine glands, specifically salivary and lachrymal glands. Primary SS (pSS) only affects these glands, while secondary SS is associated with other systemic autoimmune pathologies. SS is characterized, histopathologically, by an inflammatory lymphocytic infiltration leading to a progressive loss of the glandular secretory function. It is more common in women (9:1 versus men), mainly around 50 years old, after the menopause. The medical dentist role is very important in the diagnosis of pSS. In several cases he is the one who detects the first symptoms, in particular dry mouth, so called xerostomia. The primary syndrome doesn`t have a painful development, being dry mouth and eye dryness the most prominent clinical characteristics. The majority of the oral evidences are consequence of salivary glands hypofunction: dental caries, periodontal disease or fungal infections. Along with hyposalivation and xerostomia, communication disorders can occur like dysphagia and pharyngeal dryness leading to difficulties in speech and voice fatigue. This study is an updating of the impact of pSS in the patient`s life quality with a focus on voice and other communication disorders. There is a need for awareness of the speech problems associated with pSS referring the patients to proper professional help.